2021
DOI: 10.1177/03000605211015573
|View full text |Cite
|
Sign up to set email alerts
|

Augmented renal clearance: a retrospective, cohort study of urinary creatinine clearance in critically ill patients in the United Kingdom

Abstract: Objective Augmented renal clearance (ARC) is associated with sub-therapeutic antibiotic, anti-epileptic, and anticoagulant serum concentrations leading to adverse patient outcomes. We aimed to describe the prevalence and associated risk factors for ARC development in a large, single-centre cohort in the United Kingdom. Methods We conducted a retrospective observational study of critically unwell patients admitted to intensive care between 2014 and 2016. Urinary creatinine clearance was used to determine the AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Young age was the most commonly reported risk factor for ARC reported in nine of the studies ( 22 25 , 27 , 29 , 31 , 33 , 34 ). Other specific risk factors are listed in the Supplemental Table ( http://links.lww.com/CCX/A898 ).…”
Section: To the Editormentioning
confidence: 95%
See 1 more Smart Citation
“…Young age was the most commonly reported risk factor for ARC reported in nine of the studies ( 22 25 , 27 , 29 , 31 , 33 , 34 ). Other specific risk factors are listed in the Supplemental Table ( http://links.lww.com/CCX/A898 ).…”
Section: To the Editormentioning
confidence: 95%
“…First is the pronounced variation in onset of ARC. Patients with COVID-19 are reported to have a much-delayed onset of ARC compared with those without (13–28 d vs 1–3 d, respectively) ( 15 17 , 21 , 26 , 27 , 29 , 31 , 33 , 35 ). The duration of ARC has been less extensively studied; however, Murt et al ( 17 ) suggested ARC lasts 5 days in the COVID patients they studied, while the non-COVID-19 ARC population varies from 1 day to 3 weeks ( 15 17 , 21 , 22 , 26 , 27 , 29 , 31 , 33 , 35 ).…”
Section: To the Editormentioning
confidence: 99%
“…Nevertheless, there are several reports of augmented renal clearance (ARC) conditions in many types of critically ill patients, particularly those who are young and have experienced trauma, which may influence the performance of the predictive equations. ARC is generally defined as UCrCl >130 mL/min, which may enhance drug elimination and disturb the blood levels of several medications excreted via renal clearance ( Kawano et al, 2016 ; Johnston et al, 2021 ; Baptista et al, 2020 ; Bilbao-Meseguer et al, 2018 ). Then, there are concerns regarding the utilization of eGFR for drug dose adjustment in both overestimation and underestimation of actual GFR, which may influence the treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies showed that the at-risk groups for ARC include younger patients, especially younger male patients, with lower illness severity scores on the Sequential Organ Failure Assessment (SOFA) or Acute Physiology and Chronic Health Evaluation (APACHE) II ( Udy et al, 2013 , 2017 ; Baptista et al, 2020 ; Nei et al, 2020 ; Saito et al, 2020 ; Johnston et al, 2021 ). Disease-related risk factors include trauma, surgery, sepsis, burn, subarachnoid hemorrhage, and hematological malignancy ( Gerlach et al, 2019 ; Morbitzer et al, 2019 ; Lannou et al, 2020a ; Saito et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%